Validation of an LC–MS/MS assay for detecting relevant disaccharides from keratan sulfate as a biomarker for Morquio A syndrome. (August 2011) - Martell, Lisa Argento; Cunico, Robert L; Ohh, Jayoung; Fulkerson, Wendy; Furneaux, Richard; Foehr, Erik D
Background: Mucopolysaccharidosis IVA (MPS IVA, Morquio A syndrome) is an inherited lysosomal storage disease caused by deficiency of N -acetylgalactosamine-6-sulfatase (GALNS), an enzyme required for stepwise degradation of keratan sulfate (KS). We have developed a selective, sensitive, accurate and precise LC–MS/MS assay for the KS-derived disaccharides Galββ1–4GlcNAc(6S) and Gal(6S)ββ1–4GlcNAc(6S) in human urine and plasma using keratanase II digestion.Results: Mean accuracy was 96–106% in urine and 97–108% in plasma. Precision was high, with relative standard deviations of 1–2% (intra-day) and 2–5% (inter-day) in urine and 1–2% (intra-day) and 4–7% (inter-day) in plasma. The lower limit of quantitation was 0.026 µg/ml (plasma) and 0.104 µg/ml (urine), with a quantitation range of 0.026–5 µg/ml (plasma) and 0.104–20 µg/ml (urine).Conclusion: Clinical sample analysis in 168 MPS IVA patients and 225 healthy controls demonstrates the clinical utility of this method.